Importance of electromagnetic interactions between ICD and VAD devices—Mechanistic assessment. Issue 6 (15th January 2022) - Schnegg, Bruno; Robson, Desiree; Fürholz, Monika; Meredith, Tom; Kessler, Cassia; Baldinger, Samuel H.; Hayward, Christopher
Abstract: Background: Implanted cardioverter defibrillators (ICDs) and left ventricular assist devices (LVADs) are established interventions that prolong life in advanced heart failure, but their combination has not been demonstrated as beneficial. Electromagnetic interference (EMI) produced by a LVAD can preclude ICD interrogation with external programmers. We undertook a systematic evaluation of the LVAD–ICD interaction "in‐vitro" to clarify the extent of this interaction. Methods: Using explanted ICDs and VADs in a mock physiological rig, we assessed interrogation and reprogramming of ICD devices in the presence of a running LVAD. When connectivity between the ICD programmer and the ICD failed, we attempted three different techniques to re‐establish connectivity: (1) Electromagnetic shielding of the ICD with a pseudo‐faraday cage; (2) altering the LVAD speed; and (3) increasing the distance between the VAD and the ICD. Results: We tested a total of 24 ICDs from different manufacturers in the presence of the Heartware (HW) and HeartMate 3 (HM3) LVADs. With HW, we only observed interaction with Biotronik ICD devices at very close range (0–6 cm). With HM3, only Medtronic ICD devices showed no interaction. Interactions could be mitigated by increasing the VAD–ICD distance. Conclusions: LVADs, notably the HM3, produce EMI that interferes with the communication between an ICD and its respective programmer. This may need to be considered when choosing the type of VAD to implant in patients with a previously implanted left‐sided ICD. The only safe way to regain connectivity is to increase the distance between the VAD and the ICD, with patients raising their arm above their head. Abstract : LVADs, notably the HM3, produce EMI that interferes with the communication between an ICD and its respective programmer. The only safe way to regain connectivity is to increase the distance between the VAD and the ICD.